Applying Balanced Scorecard in Evaluating Performance: Evidence from a Food Retailer - Mediaty; Abd. Hamid Habbe; Fatimah Zahra; Sitti Aisyah; Sri Mutiah Husaini; Bashiruddin Ahmad (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2025)
Measuring employee performance through a balanced scorecard is crucial for providing a comprehensive view of an organization's effectiveness and strategic alignment. The Balanced Scorecard (BSC) is considered an instrument that can be used to effectively measure employee performance over a specific period of time. Performance appraisal not only helps companies determine the potential for human resource development but also improves employee motivation and productivity. Therefore, this study aims to empirically test and analyze employee performance measurement based on the balanced scorecard at the PHD Makassar Store. This study is a quantitative study. The population used is all employees of the PHD Makassar Store, with a sample size of 33 using the non-probability sampling method. The results of the study indicate that job satisfaction and employee turnover variables do not affect human resource performance at the PHD Bawakareng Store. Inversely, employee training and employee productivity variables affect human resource performance. This indicates that the comparison between employee input and output is running well.